Inflation Dynamics and Monetary Policy in Bolivia - Guerson, Alejandro (IMF Working Papers; Working Paper ;, 2015)
This paper explores inflation dynamics and monetary policy in Bolivia. Bolivia's monetary policy framework has been effective in stabilizing inflation in recent times. This has been a challenging task given high price volatility of key consumer goods subject to recurrent supply shocks, especially food items. Empirical testing indicates that the monetary policy framework has contributed to the stabilization of inflation, with effective transmission through the bank lending channel, while the defacto dollar peg has also played a role. Looking ahead, the current framework will be tested by the new commodity price normal and a potentially permanent adjustment in relative prices. Against this background, consideration could be given to a more flexible exchange rate policy arrangement, with short term interest rates as the main policy instrument.